Effect of Ethanol Extract of Rosella Flower Petals (Hibiscus sabdariffa L.) on Healing Cut Wounds in White Rats (Rattus norvegicus) - Pratiwi, Ade Dwi; Siahaan , Jekson Martiar; Anto, Endy Juli; Eyanoer, Putri Chairani (Indonesian Journal of Medicine, 2024)
Background: Wounds are skin disorders in the form of damage to continuity due to a pathological process, if not treated properly it can cause serious complications such as failure to heal and chronic problems due to untreated wound infections, especially post-operative infections and scar tissue. The next problem is that excessive antibiotics can cause side effects and increase the risk of antimicrobial resistance and delay wound healing. So a new strategy is needed with herbal-based therapy that has the effect of treating infections and does not cause side effects in patients. Subjects and Method: The research was conducted with a post test only randomized control group design to test macroscopic observations of the average size of the wound length, hyperemia and swelling in 30 white Wistar rats (Rattus norvegicus) after receiving ethanol extract of rosella petals (Hibiscus sabdarifa L.). The dependent variables of the study were wound closure time, hyperemia and wound swelling. The independent variable of the research was varying doses of ethanol extract of rosella flower petals (Hibiscus sabdarifa L.) 6%, 12% and 15%. The parameters assessed are the length of the wound and the macroscopic assessment of the wound. Data were analyzed using the Kruskal-Wallis test, p<0.05 was considered statistically significant. Results: Administration of Hibiscus sabdariffa L. 6%, 12% and 15% ethanol extract gel on the 12th day resulted in a significant acceleration of the wound healing process (p=0.024). There was a significant difference between negative control (Mean=3,281 mm ; SD=1,681 mm), positive control (Mean=2,813 mm ; SD=1,106 mm), 6% Rosella flower petal extract gel (Mean=2,916 mm ; SD=1,224 mm ), 12% (Mean=1,290 mm ; SD=1,098 mm), and 15% (Mean=1,035 mm ; SD=0.952 mm) (p=0.024), in the macroscopic assessment there was no significant difference in the wound healing process on day 3, 6, 9, 12 and 15 except for signs of swelling on days 6 (p=0.038) and 9 (p=0.038) which had a significant difference compared to controls. Conclusion: Administration of Hibiscus sabdariffa L. 15% ethanol extract gel had the fastest time in wound closure and healing (Mean=1.035 mm ; SD=0.952 mm) for 12 days (p=0.024), the longest time in wound closure and healing was the negative control (gel placebo) (Mean=0.976 mm ; SD=1.103 mm) namely for 15 days (p=0.158). Keywords: Wound healing, Roselle, Gel Ekstrak Etanol, Hyperemia